Reduction of heart rate variability in hypertensive elderly. (2nd November 2017) - de Andrade, Paulo Evaristo; do Amaral, Joice Anaize Tonon; Paiva, Laércio da Silva; Adami, Fernando; Raimudo, Juliana Zangirolami; Valenti, Vitor Engrácia; Abreu, Luiz Carlos de; Raimundo, Rodrigo Daminello
Abstract: Introduction: The elderly population grows globally every day, and along with it the incidence of high blood pressure also grows, following these data scientists seek tools to improve the health of this population, a widely used tool for assessing cardiovascular function is the heart rate variability(HRV), that is a mecanism that allows the investigation of oscillations in the intervals between consecutive heart beats (RR intervals). There are already studies on the autonomic nervous system in the elderly population, however, these studies investigated normotensive patients and there is little research in hypertensive patients. Aim: To compare the cardiac autonomic modulation between healthy elderly and hypertensive elderly. Method: The total sample was 80 elderly people- 40 healthy elderly and 40 elderly (HBP). Anthropometric data, HRV analysis and IPAQ questionnaire were collected. For the analysis of cardiac modulation data in the time domain (pNN50, SDNN and RMSSD) and frequency domain (LF and HF). The geometric analysis (RRtri, TINN, SD1, SD2 and SD1/SD2 ratios). Results: In the time domain the MeanRR index presented a HAS increase 832.35 ± 104.46 ms vs control 782.73 ± 112.78 ms ( p = 0.040). In the SDNN, there was a 58.35ms decrease vs the SAH 43.15 ms ( p = 0.030). In the frequency domain, HF decreased control 247.00 ms2 vs HAS 157.00 ms2 ( p = 0.002). In the geometric, the TINN and SD2 in the HAS group decreased in relation to the control from 203.38 ± 80.26 ms to 161.83 ± 53.25 ms ( p = 0.018) and from 71.95 ms to 59.40 ms ( p = 0.051). The mean SD1/SD2 ratio showed an increase between the Control and SAH groups from 0.22 ± 0.10 to 4.09 ± 1.18 and there was a statistical difference ( p = 0.001). Conclusion: Hypertensive elderly patients present decreased heart rate variability and decreased parasympathetic modulation when compared to normotensive elderly.